A designed synthesis of multifunctional carbon nanoframes for simultaneous imaging and synergistic chemo-photothermal cancer therapy. (11th December 2017) - Wei, Xuan; Zhang, Lingyu; Li, Shengnan; Chen, Xiangjun; Zhang, Manjie; Wang, Chungang; Wang, Tingting; Li, Lu
Abstract : A simple synthetic route was developed to fabricate mesoporous carbon nanoframes for simultaneous photoacoustic imaging and synergistic chemo-photothermal cancer therapy. Abstract : Owing to their small size and unique optical properties, carbon nanomaterials have attracted considerable attention due to their promising biomedical applications. In this work, we report a silica (SiO2 ) protected calcination strategy to fabricate mesoporous carbon nanoframes (mCNFs) from zeolitic imidazolate framework-8 (ZIF-8) precursors. The resulting mCNFs have many merits including drug loading capability, excellent photothermal efficiency (21%), dual pH/near-infrared (NIR) responsive controlled drug release and good biocompatibility. When 5-FU-loaded mCNFs were subjected to NIR irradiation, a burst release of 5-FU occurs owing to the heat produced by the mCNFs. Furthermore, mCNFs are successfully employed for photoacoustic imaging (PAI) and synergistic chemo-photothermal cancer therapy. Taken together, mCNFs can be developed as a promising theranostic agent for cancer treatment.